Dynamic of Recovery from Marriage Anxiety Through Islamic Integrated Cognitive Behavior Therapy (IICBT) Intervention in Individual Counseling - Siti Aisyah Wahyuni; Nurjannah Nurjannah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
The phenomenon of fear of marriage is increasingly experienced by young adults, particularly as a result of traumatic relational experiences such as failed serious relationships and betrayal by a partner. This condition causes ongoing anxiety that affects an individual's readiness to commit to marriage. Therefore, a counseling approach is needed that not only focuses on psychological aspects but also integrates spiritual dimensions in accordance with the belief system of Muslim clients. This study aims to analyze the dynamics of recovery from the trauma of fear of marriage through Islamic Integrated Cognitive Behavior Therapy (IICBT) intervention in individual counseling. This study uses a qualitative approach with a case study method on one early adult Muslim client who experiences fear of marriage. Data collection techniques included in-depth interviews, observations, and counseling process notes, while data analysis was conducted thematically. The results showed that the application of IICBT was effective in facilitating positive changes in the client's cognitive, emotional, behavioral, and spiritual aspects. The client was able to reduce negative thoughts, achieve inner peace, and interpret marriage as a form of worship and a process full of wisdom.